Electrochemical Deoxygenation of N-Heteroaromatic N-Oxides - Xu, P.; Xu, H.-C. (Synlett, 2019)
An electrochemical method for the deoxygenation of N-heteroaromatic N-oxide to give the corresponding N-heteroaromatics has been developed. Several classes of N-heterocycles such as pyridine, quinoline, isoquinoline, and phenanthridine are tolerated. The electrochemical reactions proceed efficiently in aqueous solution without the need for transition-metal catalysts and waste-generating reducing reagents.
Keywords: reduction; organic electrosynthesis; deoxygenation; electrolysis; heterocycles